PENGARUH BRAND AWARENESS DAN PROMOSI ONLINE MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN DI KOTA BATAM - Jennifer, Jennifer -; S.E., M.Si., Asron Saputra (SCIENTIA JOURNAL, 2021)
The main objective of the study was to analyze the Effect of Brand Awareness and Promotion on Media Sosial Instagram on Consumer Buying Interest at Batam City. In this study there were 100 respondents who were used to be analyzed. Multiple regression analysis was used in this test. The independent variable used is brand awareness and the dependent variable is consumer buying interest. There are three results in this research that were obtained and it resulted that brand awareness has a positive and significant effect on buying interest, with a significance level of 0.000 < 0.05. this means the first hypotesis isaccepted. Promotion on media sosial has a positive and significant effect on buying interest, with a significance level of 0.000 < 0.05, this means that the second hypothesis is accepted. While simultaneously brand awareness and promotion on media sosial have a significant effect on buying interest with a significant level of 0.000 < 0.05 this means the third hypothesis is accepted.